PENGARUH MULTIMEDIA LECTORA INSPIRE PADA PEMBELAJARAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR TERMOKIMIA - Yolanda Maria Lumban Gaol; A. Darmana A. Darmana (Jurnal Sains Riset, 2022)
This study aims to determine: (1) the effect of multimedia Lectora inspire on problem-based learning (PBL) on thermochemistry learning outcomes; (2) Students' responses to the multimedia Lectora inspire on PBL thermochemical material. The population in this study were all students of class XI MIPA at SMA Negeri 7 Medan. Samples were taken by purposive sampling as many as 2 classes. The experimental class was taught using Lectora inspire multimedia and the control class was taught without Lectora inspire. Both classes use the PBL model. The test instrument used was a test of thermochemistry learning outcomes in the form of multiple choice as many as 20 questions, while student responses were measured by questionnaires. Data were analyzed by normality, homogeneity, and hypothesis testing t-test with a significance level of 0.05. The results of data analysis show that (1) there is an influence of the multimedia Lectora inspire with problem based learning (PBL) learning model on student chemistry learning outcomes; (2) The student's response to the multimedia Lectora inspire with the problem based learning (PBL) model on thermochemical material shows a percentage result of 76.04% and is categorized as good.Keywords: lectora inspire, problem based learning, learning outcomes, student response